THU0521 Dual Neutralization of TNF and IL-17 with A Dvd-Ig Protein is Efficacious in Collagen Induced Arthritis. (10th June 2014) - Cuff, C.; Bryant, S.; Hugunin, M.; Kamath, R.; Voss, J.; Olson, L.; Hsieh, C.-M.
Abstract : Background: TNF blockade has provided significant benefit to many patients with rheumatoid arthritis. Nonetheless, a substantial unmet medical need remains for patients who do not respond adequately to this treatment. We and others have demonstrated that dual neutralization of TNF and IL-17 provides greater efficacy than blocking either cytokine alone in mouse collagen induced arthritis 1, 2, 3 . Objectives: The goal of these studies was to determine whether an anti-TNF/IL-17 Dual Variable Domain immunoglobulin (DVD-Ig™) protein would be efficacious in a pre-clinical model of arthritis. Methods: A surrogate anti-mouse TNF and IL-17 DVD-Ig™ protein was engineered from two variable domains that bind TNF and IL-17, respectively. The resulting DVD-Ig™ has high affinity and potency to both targets and is capable of simultaneous binding of TNF and IL-17 as determined by surface plasmon resonance. The efficacy of this anti-mouse TNF/IL-17 DVD-Ig™ molecule was tested in the mouse collagen induced arthritis model. Animals were treated with vehicle anti-TNF antibody (Ab) (8C11, 12 mg/kg), anti-IL-17 Ab (MAB421, 12 mg/kg), anti-TNF + anti-IL-17 Abs (12/12 mg/kg), or an anti-mouse TNF/IL-17 DVD-Ig™ protein (16 mg/kg) twice a week for 3 weeks beginning at the onset of disease. The effect on disease was measured by paw swelling, histologic evaluation, as well as micro-CT measurement of bone volume. Results: Neutralization of either mouse TNF or IL-17 by their respective Abs alone resulted in a significant but partial inhibition of paw swelling (43 and 24%, respectively, p<0.05). However, neutralization of both cytokines by administration of a combination of anti-TNF and anti-IL-17 mAbs significantly reduced arthritic score to a greater extent 64%; p<0.05) and was also more effective at preventing bone destruction vs treatment with anti-TNF alone as determined by micro-CT analysis (80% vs 49 or 53%, p<0.05). Treatment with an anti-mouse TNF/IL-17 DVD-Ig™ protein inhibited inflammation, swelling, cartilage and bone destruction to a similar level as that achieved with the combination treatment with both Abs. Conclusions: These data demonstrate that dual blockade of TNF and IL-17 with a DVD-Ig™ molecule is efficacious in a pre-clinical model of arthritis and support the rationale to clinically evaluate the anti-human TNF/IL-17 DVD-Ig protein, ABT-122, in rheumatoid arthritis and other inflammatory disorders. References: Cuff et al 2013 Annual Meeting, Abstract 948. Koenders et al., Arthritis Rheum. 2011;63(8):2329-39. Alzabin et al Ann Rheum Dis. 2012;71(10):1741-8. Disclosure of Interest: : C. Cuff Shareholder of: Abbvie, Employee of: AbbVie Bioresearch Center, S. Bryant Employee of: AbbVie Bioresearch Center, M. Hugunin Shareholder of: Abbvie, Employee of: AbbVie Bioresearch Center, R. Kamath Shareholder of: Abbvie, Employee of: AbbVie Bioresearch Center, J. Voss Shareholder of: Abbvie, Employee of: AbbVie Bioresearch Center, L. Olson Shareholder of: Abbvie, Employee of: AbbVie Bioresearch Center, C.-M. Hsieh Shareholder of: Abbvie, Employee of: AbbVie Bioresearch Center DOI: 10.1136/annrheumdis-2014-eular.5383